2003
DOI: 10.1080/1363849031000109516
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral atrophy following shaken impact syndrome and other non-accidental head injury (NAHI)

Abstract: A large proportion of the cohort (93.8%) develops acquired microcephaly after an inflicted head injury and cerebral atrophy is responsible in half of these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…There is a paucity of data in children. In infants with nonaccidental head injury, acquired microcephaly was found in 15 of 16 children seen after a median follow-up period of almost 18 months [Lo et al, 2003]. In 8 of the 15 children with microcephaly, the cause was cerebral atrophy.…”
Section: Imaging Late Outcome After Tbi In Childhoodmentioning
confidence: 95%
“…There is a paucity of data in children. In infants with nonaccidental head injury, acquired microcephaly was found in 15 of 16 children seen after a median follow-up period of almost 18 months [Lo et al, 2003]. In 8 of the 15 children with microcephaly, the cause was cerebral atrophy.…”
Section: Imaging Late Outcome After Tbi In Childhoodmentioning
confidence: 95%
“…7) Shaken baby syndrome (SBS) is a form of abuse that can cause severe injuries such as subdural hematoma (SDH), subarachnoid hemorrhage, hemorrhagic contusion, and/or diffuse axonal injury. 8,12,13) We describe a case of SBS manifesting as chronic SDH detected by magnetic resonance (MR) imaging, diffusionweighted MR imaging, and single photon emission computed tomography (SPECT).…”
Section: Introductionmentioning
confidence: 99%
“….'. Contrary to the clinical evidence of severe and widespread brain injury and subsequent generalized atrophy following early injury for example [6], it is far too often suggested that the infant is developing normally; that there are no sequelae and certainly no need for intervention. Lawyers guided by such expert opinion may seek limited financial damages or provision for the child.…”
Section: Introductionmentioning
confidence: 84%